Answer:
(1, 1), (2, 2), (3, 3)
Step-by-step explanation:
it is increasing at a constant rate.
The first sentence → x - 2y = -1
the second one → 3x - 2y = -3
multiply the first one by -1
you can get → -x + 2y = 1
plus two sentences together
you can get → 2x = -2
so you are able to know that x = -1
and y = 0
Answer:
The value remain unchanged.
Step-by-step explanation:
By Z score, we mean:
Z =
, if we substitute the given values of mean and standard deviation, we obtain the z score value. That is,
Z =
= 85/12 = 7.083333.
NB: We assume that mean and standard deviation are in the same units.
Answer:
Step-by-step explanation:9m -3m +2n = 6m+2n